2015
DOI: 10.1016/j.geomorph.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Gaining insight into regional coastal changes on La Réunion island through a Bayesian data mining approach

Abstract: International audienceRecent works have highlighted the interest in coastal geographical databases - collected for coastal management purposes - for obtaining insight into current shoreline changes. On La Réunion, a tropical volcanic high island located in the Southern Indian Ocean, a dataset is available which describes shoreline changes, the coastal geomorphology and the presence of anthropic structures. This database is first supplemented with information on the exposure of each coastal segment to energetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In the study [10] authors offered a general overview of the recent works undertaking the predictive and descriptive tasks in the building field, with the aim of improving building performance. On the other hand, the works [11,12] confirmed the considerable potential of Bayesian networks to explore coastal databases. The software industry has also benefited from DM techniques as seen in [13], where Ahmed H. Yousef proposed a solution architecture that enhances software development based on data in software repositories and presented a benchmark that provides an ensemble of DM models in the defective modules prediction problem and compares the results.…”
Section: Related Workmentioning
confidence: 87%
“…In the study [10] authors offered a general overview of the recent works undertaking the predictive and descriptive tasks in the building field, with the aim of improving building performance. On the other hand, the works [11,12] confirmed the considerable potential of Bayesian networks to explore coastal databases. The software industry has also benefited from DM techniques as seen in [13], where Ahmed H. Yousef proposed a solution architecture that enhances software development based on data in software repositories and presented a benchmark that provides an ensemble of DM models in the defective modules prediction problem and compares the results.…”
Section: Related Workmentioning
confidence: 87%
“…Bulteau et al. (2015) included the presence of estuaries as a new variable in the BN and ranked this variable as the second significant next to the geomorphology. Sahin et al.…”
Section: Introductionmentioning
confidence: 99%
“…A similar spatial BN as Gutierrez et al (2011) was constructed but trained with a Eurasian data set by Yates and Le Cozannet (2012), which found that SLR was of secondary importance on shoreline change after geomorphology. Bulteau et al (2015) included the presence of estuaries as a new variable in the BN and ranked this variable as the second significant next to the geomorphology. Sahin et al (2019) applied a spatial BN to a reef island in Vanuatu by extracting data for different variables either from globally available data sets or by manual inspection.…”
mentioning
confidence: 99%
“…Here, we explore how different groups of coastal sites may have contrasting coastal behaviors, following the clustering approach of Gutierrez et al (2011). For example, the coastal database of the eastern United States shoreline was used to detect similarities between the spatial patterns of sea-level rise and shoreline changes, which provide insight into the role of sea-level rise in shoreline erosion (e.g., Gutierrez et al, 2011;Bulteau et al, 2015). Less attention has been given to the temporal evolution of shoreline changes.…”
Section: Introductionmentioning
confidence: 99%